Impact of wearing a facial covering on aerobic exercise capacity in the COVID-19 era: is it more than a feeling? - Kampert, M.; Singh, T.; Finet, J. E. (Clinical Research in Cardiology, 2020)
In this issue of Clinical Research in Cardiology, Drs. Fiken-zer and colleagues [1] should be acknowledged for their timely study focused on examining how `cardiopulmonary exercise capacity` may be impacted by wearing a nose and mouth facial covering during cardiopulmonary exercise test-ing (CPET). They are the first to report in a randomized-con-trolled cross-over study design that when CPET is performed by healthy young-to-middle aged adult men while wearing an FFP2/N95 mask (ffpm), and to a lesser extent with a surgical mask (sm), key exercise measurements, including peak oxygen uptake (V?O2peak), maximum Power (Pmax), and peak minute ventilation (V?E) do not increase to levels demonstrated during CPET with no mask (nm) [1].